Laws of love and logic : a novel - Curtis, Debra, 1963- (Ballantine Books, 2026)
In the serene town of Portsmouth, Rhode Island, Lily Webb is deeply in love with a charismatic boy, a college-bound quarterback whose spectacular athletic talents are matched only by his fierce devotion. But their dreams of a life together are cut short when his passionate protectiveness leads to an irrevocable choice--one that tearsthem apart and leads Lily down a path of heartbreak from which she may never recover.